Efficacy and safety of paracetamol, phenylephrine, chlorpheniramine maleate and sodium citrate in Indian paediatric patients with common cold: an active post-marketing surveillance study - Kiran, Mayuresh D.; Pawaskar, Lalit J.; Waghambare, Pramita D.; Singh, Aakansha V. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: The common cold, mainly caused by viruses, brings discomfort to children with symptoms like sneezing, congestion, runny nose, and sore throat. As no specific antiviral treatments are available to relieve common cold symptoms, it is typically managed using decongestants, antihistamines, and antipyretics. This study aims to assess the safety and efficacy of a fixed-dose combination (FDC) of paracetamol, phenylephrine, chlorpheniramine maleate and sodium citrate in children aged 2 to 12 years with common cold. Methods: This non-randomized, open-label, non-comparative, active post-marketing surveillance (PMS) study was conducted across multiple centres in India, involving 417 patients. The study assessed efficacy using the total symptom score (TSS) scale over 5 days with visits on days 1, 3, and 5. Safety was evaluated based on adverse events reported by patients on days 3 and 5 of the trial. Results: Initially, 417 patients were enrolled in the active PMS, of which 309 completed the study. The mean TSS showed a notable decrease from 8.95 at visit 1 to 0.19 at visit 3, depicting a significant reduction i.e., 97.90% as compared to baseline. At visit 1, most patients (95.79%) exhibited severe symptoms, whereas by visit 3, 83.82% were symptom-free, with only 16.18% experiencing mild symptoms. Conclusions: This active PMS study examined the safety and efficacy of an FDC of paracetamol, phenylephrine, chlorpheniramine maleate and sodium citrate in treating common cold in children in India. The findings indicate a significant reduction in symptoms, with many patients becoming symptom-free by the third visit, demonstrating its efficacy and safety.